2011
DOI: 10.1109/msp.2011.942473
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention in Quality Assessment

Abstract: P erceptual quality metrics are widely deployed in image and video processing systems. These metrics aim to emulate the integral mechanisms of the human visual system (HVS) to correlate well with visual perception of quality. One integral property of the HVS is, however, often neglected: visual attention (VA) [1]. The essential mechanisms associated with VA consist mainly of higher cognitive processing, deployed to reduce the complexity of scene analysis. For this purpose, a subset of the visual information is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 69 publications
(113 reference statements)
0
61
0
Order By: Relevance
“…Eye-tracking data is the most typical psychophysical ground truth for visual saliency models [18]. To evaluate saliency models, each model's saliency map is compared with recorded gaze locations of the subjects.…”
Section: B Eye-tracking Video Datasetsmentioning
confidence: 99%
“…Eye-tracking data is the most typical psychophysical ground truth for visual saliency models [18]. To evaluate saliency models, each model's saliency map is compared with recorded gaze locations of the subjects.…”
Section: B Eye-tracking Video Datasetsmentioning
confidence: 99%
“…Recently, researchers have gradually found that VS is closely relevant to the image's perceptual quality. Various methods have been attempted to integrate VS information into IQA metrics [4]. These methods demonstrate that a VS-weighted pooling strategy could perform better than the simple "mean" scheme.…”
Section: Two Visual Saliency Modelsmentioning
confidence: 99%
“…Consequently, in this paper, we attempt to extent TMQI by proposing a novel VS-based pooling strategy. Specifically, in our method, we use VS as a weight map, which is inspired by its successful use on IQA [4,5]. The experimental results demonstrate that the VS-based pooling strategy can achieve significantly better performance than the simple "mean" that used in TMQI.…”
Section: Introductionmentioning
confidence: 99%
“…A saliency map (SM) representative for visual attention is derived from gaze patterns recorded from eye-tracking (see [1], [4] and [6]). It is constructed adding to each fixation location a Gaussian patch, which approximates the size of the fovea in the human eye (about 2 of visual angle, corresponding to a σ of 45 pixels for the Gaussian for all three experiments).…”
Section: B Variation In Saliency Among Individualsmentioning
confidence: 99%